012 Differential roles of the plasma membrane calcium pump isoforms 1 and 4 in modulating cardiac contractility. (22nd September 2015) - Shaheen, M A; Mohamed, T M A; Zi, M; Prehar, S; Alatwi, N; Hegab, Z; Baudoin, F; Emerson, M; Oceandy, D; Cartwright, E J; Neyses, L
Abstract : Heart failure is a syndrome currently affecting almost one million people in the UK. Abnormal calcium handling is one the characteristic features of heart failure. The plasma membrane calcium pump (PMCA) is one of the calcium transporters in the cardiomyocytes. Two isoforms of PMCA, PMCA1 and 4, are expressed in the myocardium. Our group has shown previously that PMCA4 modulates the beta-adrenergic response in the heart through its interaction with nNOS. Currently, in order to elucidate the physiological importance of both PMCA isoforms in the modulation of cardiac contractility we generated mice carrying a genetic deletion of either PMCA1 or PMCA4. Given that PMCA4 is a calcium extrusion pump it was unexpected that in vivo basal contractility was enhanced in PMCA4 KO mice (dP/dtmax in 8049±628 vs 6604±296 mmHg/s in KO and WT respectively, p<0.05, n=10). This enhanced contractility was imitated in WT mice by injecting the nNOS specific inhibitor (L-NPA). Ca 2+ transients in cardiomyocytes from PMCA4 KO mice showed an increase in amplitude (298.8±24.3 nM calcium vs 492.2±28.2 nM calcium in WT and KO respectively; p<0.05, n=8) with no change in the rate of Ca 2+ decay. Again, this phenotype was imitated by nNOS specific inhibition in WT adult CMC. Although, there is no difference in total nNOS protein expression between PMCA4 KO and WT, the nNOS localisation and activity at the sarcolemmal membrane was decreased by 52% in PMCA4 KO. Intracellular cardiac cGMP levels in PMCA4 KO were markedly decreased (619±16.7 fmol/mg protein in KO vs 713.4±24.2 fmol/mg protein in WT) suggesting that the phenotype was likely through nNOS modulation. Since the global deletion of PMCA1 is embryonic lethal, we generated PMCA1 cardiac-specific knockout mice (PMCA1cko) using Cre/LoxP technology. PMCA1cko showed a reduction in the rate of relaxation (logistic τ; 6.9±0.34 vs 5.8±0.29 ms in PMCA1cko and PMCA1flox/flox control respectively; p<0.05, n=11) without any change in cardiac contractility. On the contrary to PMCA4 KO, cardiomyocytes from PMCA1cko revealed a decreased rate of Ca 2+ decay (τ, 0.201±0.009 vs 0.164±0.006 ms in PMCA1cko and PMCA1flox/flox respectively; p<0.05, n=16), while Ca 2+ transient amplitude remained unchanged. The nNOS protein expression, localisation and activity in PMCA1cko mice were similar to those in PMCA1flox/flox. In conclusion, our results suggest differential rather than redundant roles of the cardiac PMCAs. PMCA4 regulates cardiac signalling through modulation of membrane nNOS activity, while PMCA1 modulates fine tuning of diastolic calcium in the excitation-contraction coupling. The use of non-isoform-specific inhibitors in previous work was unable to detect these differential roles as the effects of PMCA1 and 4 inhibition cancel each other out, at least in part.